Transparency of open data ecosystems in smart cities: Definition and assessment of the maturity of transparency in 22 smart cities - Lněnička, Martin; Nikiforova, Anastasija; Luterek, Mariusz; Azeroual, Otmane; Ukpabi, Dandison; Valtenbergs, Visvaldis; Máchová, Renáta (My University, 2022)
This paper focuses on the issue of the transparency maturity of open data ecosystems seen as the key for the development and maintenance of sustainable, citizen-centered, and socially resilient smart cities. This study inspects smart cities’ data portals and assesses their compliance with transparency requirements for open (government) data. The expert assessment of 34 portals representing 22 smart cities, with 36 features, allowed us to rank them and determine their level of transparency maturity according to four predefined levels of maturity - developing, defined, managed, and integrated. In addition, recommendations for identifying and improving the current maturity level and specific features have been provided. An open data ecosystem in the smart city context has been conceptualized, and its key components were determined. Our definition considers the components of the data-centric and data-driven infrastructure using the systems theory approach. We have defined five predominant types of current open data ecosystems based on prevailing data infrastructure components. The results of this study should contribute to the improvement of current data ecosystems and build sustainable, transparent, citizen-centered, and socially resilient open data-driven smart cities.
Transparentnost ekosystémů otevřených dat v chytrých městech: Definice a hodnocení vyspělosti transparentnosti ve 22 chytrých městech
Keywords: open data; smart city; transparency; maturity; ecosystem; expert assessment; otevřená data; chytré město; transparentnost; vyspělost; ekosystém; expertní hodnocení